Inter-Species Comparative Analysis of Components of Soluble Sugar Concentration in Fleshy Fruits - Dai, Zhanwu; Wu, Huan; Baldazzi, Valentina; van Leeuwen, Cornelis; Bertin, Nadia; Gautier, Hélène; Wu, Benhong; Duchêne, Eric; Gomès, Eric; Delrot, Serge; Lescourret, Françoise; Génard, Michel (Frontiers in Plant Science, 2016)
The soluble sugar concentration of fleshy fruit is a key determinant of fleshy fruit quality. It affects directly the sweetness of fresh fruits and indirectly the properties of processed products (e.g. alcohol content in wine). Despite considerable divergence among species, soluble sugar accumulation in a fruit results from the complex interplay of three main processes, namely sugar import, sugar metabolism, and water dilution. Therefore, inter-species comparison would help to identify common and/or species-specific modes of regulation in sugar accumulation. For this purpose, a process-based mathematical framework was used to compare soluble sugar accumulation in three fruits: grape, tomato and peach. Representative datasets covering the time course of sugar accumulation during fruit development were collected. They encompassed 104 combinations of species (3), genotypes (32), and growing conditions (19 years and 16 nutrient and environmental treatments). At maturity, grape showed the highest soluble sugar concentrations (16.5-26.3 g /100 g FW), followed by peach (2.2 to 20 g /100 g FW) and tomato (1.4 to 5 g /100 g FW). Main processes determining soluble sugar concentration were decomposed into sugar importation, metabolism and water dilution with the process-based analysis. Different regulation modes of soluble sugar concentration were then identified, showing either import-based, dilution-based, or import and dilution dual-based. Firstly, the higher soluble sugar concentration in grape than in tomato is a result of higher sugar importation. Secondly, the higher soluble sugar concentration in grape than in peach is due to a lower water dilution. The third mode of regulation is more complicated than the first two, with differences both in sugar importation and water dilution (grape vs cherry tomato; cherry tomato vs peach; peach vs tomato). On the other hand, carbon utilization for synthesis of non-soluble sugar compounds (namely metabolism) was conserved among the three fruit species. These distinct modes appear to be quite species-specific, but the intensity of the effect may significantly vary depending on the genotype and management practices. These results provide novel insights into the drivers of differences in soluble sugar concentration among fleshy fruits.